2014
DOI: 10.3109/02688697.2014.987215
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic intracerebellar haematoma: To operate or not to operate?

Abstract: Surgery in patients with the mentioned risk factors remains debatable and should be approached cautiously. Larger multi-institutional and meta-analytic studies are required to study and statistically establish the factors which might be associated with poor outcome in these patients. An algorithm which may be used in the management of traumatic intracerebellar haematoma patients is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…In accordance with previous studies on this topic our data showed GCS at initial presentation to be the most predictive clinical tool 5,6,7,21,23,25 . Domenico d'Avella et al 7 suggest that A GCS score of less than 8 was the most powerful adverse prognostic factor (58.78% probability of poor outcome as sole covariate) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with previous studies on this topic our data showed GCS at initial presentation to be the most predictive clinical tool 5,6,7,21,23,25 . Domenico d'Avella et al 7 suggest that A GCS score of less than 8 was the most powerful adverse prognostic factor (58.78% probability of poor outcome as sole covariate) .…”
Section: Discussionsupporting
confidence: 92%
“…In this study fall from bike and pillan rider are the most common mechanism of injury. Bhardwaj et al has 15/21( 71.14%) 5 , Harsh et al has 15/23 ( 65.21%) 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bullock and Chang. [13], [14] had observed that ICP monitoring was tried in this study, but they observed that it was unable to predict the late onset sudden rise in pressure instead of ICP monitoring obliteration of basal cisterns pears to be more reliable indicator for severity of injury we agree with the observation of above study Virat Harsh et al and D. D'evella et al [15], [16] noted that the poor prognosis was observed in the patients having GCS-7 or below. In our study also, similar results were observed.…”
Section: Masseffectsupporting
confidence: 86%
“…Compared with traumatic brain injury, traumatic intracerebellar hemorrhage (TICH) has only a few small series of cases being reported [1][2][3][4][5]. Although TICH is a rare entity, it is associated with high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%